Chelerythrine Attenuates the Inflammation of Lipopolysaccharide-Induced Acute Lung Inflammation Through NF-κB Signaling Pathway Mediated by Nrf2 - Lu Fan; Ye Fan; Li Liu; Weiwei Tao; Xin Shan; Yu Dong; Lin Li; Sen Zhang; Hanqing Wang; Hanqing Wang (Frontiers Media S.A., 2018)
Chelerythrine (CH), is a kind of benzo[c] phenanthridine alkaloid isolated from plants such as Chelidonium, with pharmacological activities as antitumor, antibiosis and anti-inflammation. However, few studies have demonstrated whether CH could protect against lipopolysaccharide (LPS)-induced acute lung injury (ALI), and the underlying mechanism is also uncertain. The purpose of the present study was to investigate the anti-inflammatory effects of CH on LPS-induced ALI in mice and in RAW264.7 cells. In this study, we demonstrated that treatment with CH significantly ameliorated LPS-induced pathological changes in the lung. CH also attenuated LPS-induced W/D ratio, inflammatory cell infiltration. Meanwhile, LPS-induced Tumor necrosis factor-alpha (TNF-α), interleukin 6 (IL-6), and interleukin 1β (IL-1β) production and oxidative stress were markedly suppressed by CH. Furthermore, western blot showed that CH suppressed LPS-stimulated inflammation of RAW264.7 cells through activation of nuclear factor kappa-B (NF-κB) pathway. Knocking down of nuclear factor erythroid 2-related factor 2 (Nrf2) led to the reduction of nuclear translocation of the NF-κB p65, which triggered inflammation. These experimental results provided evidence that CH could be a potential therapeutic candidate for the intervention of ALI caused by LPS.